Discriminating data correlation, neighborhoods, and the new politics of recognition - Chun, Wendy Hui Kyong 1969- (The MIT Press, 2021)
"Chun investigates the centrality of race, gender, class, and sexuality to "Big Data" and network analytics"--
Keywords: Diskriminierung; Big Data; Algorithmus; Big data / Social aspects; Artificial intelligence / Social aspects; Privacy, Right of